2018
DOI: 10.1002/aenm.201803078
|View full text |Cite
|
Sign up to set email alerts
|

Deactivating Defects in Graphenes with Al2O3 Nanoclusters to Produce Long‐Life and High‐Rate Sodium‐Ion Batteries

Abstract: LIBs), delivers very limited reversible capacity in SIBs due to its inability to form stable low-stage graphite intercalation compounds (GICs). [4,5] Thus, most research has turned to nongraphitic carbons including nanocarbons and hard carbons, [6][7][8][9][10] whose capacities are significantly higher than graphite. It has been found that the structure could be well controlled to realize the high efficiency and reversibility. Our group has reported that the commercial carbon molecular sieves with abundant ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 81 publications
1
44
0
Order By: Relevance
“…The value of I D /I G decreases with ALD coating cycles increase, which was because of the coverage of defective sites by the Al 2 O 3 coating. Defective sites can efficiently adsorb ions and then form strong bonds with the oxides …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of I D /I G decreases with ALD coating cycles increase, which was because of the coverage of defective sites by the Al 2 O 3 coating. Defective sites can efficiently adsorb ions and then form strong bonds with the oxides …”
Section: Resultsmentioning
confidence: 99%
“…Defective sites can efficiently adsorb ions and then form strong bonds with the oxides. [30][31][32][33] The elements' chemical bonding states and surface contents of 20-ALD-NG and 50-ALD-NG were measured by XPS. Figure 2C is a part of the original XPS survey spectra.…”
Section: Resultsmentioning
confidence: 99%
“…But, the lack of suitable electrode materials strictly hinders the development of metal‐ion batteries. Graphene, a class of superior thermal and electrical conductors, can not only act as a conductive filler but also form the desirable nanocomposite electrode structures in conjunction with carbon nanotubes, transition metal oxides, and so forth to enhance ion infusion, electron transfer, and alleviate the volume expansion 80‐82,90,91‐96 . The strategy for the feasible nanostructured assembly of a three‐dimensional porous graphene/niobia (Nb 2 O 5 ) composite was applied by Sun et al 83 to prepare the 3D electrode architecture delivering high areal capacity and high‐rate capability at practical levels of mass loading.…”
Section: The Versatile Applications Of 2d Group‐iva Materialsmentioning
confidence: 99%
“…Graphene, a class of superior thermal and electrical conductors, can not only act as a conductive filler but also form the desirable nanocomposite electrode structures in conjunction with carbon nanotubes, transition metal oxides, and so forth to enhance ion infusion, electron transfer, and alleviate the volume [79] expansion. [80][81][82]90,[91][92][93][94][95][96] The strategy for the feasible nanostructured assembly of a three-dimensional porous graphene/ niobia (Nb 2 O 5 ) composite was applied by Sun et al 83 to prepare the 3D electrode architecture delivering high areal capacity and high-rate capability at practical levels of mass loading. Subsequently, Zhao et al 84 found that densely packed Li x M/graphene foils (M = Si, Sn, or Al) would serve as air-stable and freestanding anodes guaranteeing stable structures and exceptional cyclabilities ( Figure 10).…”
Section: Batteriesmentioning
confidence: 99%
“…Nonetheless, the larger radius of sodium (1.02 Å) compared with lithium (0.76 Å) causing serious volume expansion during the storage/release processes . In addition, the standard reduction potential of sodium (−2.71 V vs standard hydrogen electrode (SHE)) is also more positive than lithium (−3.04 V vs SHE), hence simultaneous causing low operating voltage and poor energy density . To further promote the advance progress of RT‐SIBs technologies, it is urgent to develop appropriate host materials for sodium storage …”
Section: Introductionmentioning
confidence: 99%